Understanding the utilization of primary health care services by Indigenous men: a systematic review - Kootsy Canuto; Alex Brown; Gary Wittert; Stephen Harfield (BMC, 2018)
Abstract Background Aboriginal and Torres Strait Islander men experience worse health outcomes and are the most marginalized and disadvantaged population group in Australia. Primary health care services are critical to providing both clinical and social and emotional support, however, remain underutilized by Aboriginal and Torres Strait Islander men. This review aims to better understand the utilization of primary health care services by Indigenous men and assess the effectiveness of strategies implemented to improve utilization. Methods A four-step search strategy was employed across four databases to find peer-reviewed publications and grey literature from Australia, New Zealand, Canada and America. The search began in March 2015 and included the following databases PubMed, CINAHL, Informit (Indigenous collection) and Embase. Additional databases and websites were also searched for grey literature, reference lists of included publications were searched for additional studies and relevant experts were consulted. Results The literature search found seven articles that met the inclusion criteria; four describing three research projects, plus three expert opinion pieces. The search was unable to find published research on strategies implemented to improve primary health care utilization by Indigenous men. There is limited published research focused on the utilization of primary health care by Indigenous men. From the identified papers Indigenous men described factors impacting utilization which were categorized into three primary organizing themes; those related to health services, the attitudes of Indigenous men and knowledge. It is evident from the identified papers that improvements in Indigenous health can only occur if future programs are developed in collaboration with health services and Indigenous men to address differing requirements. Conclusions Currently, health systems in Australia are limited in their ability to improve the health and wellbeing of Aboriginal and Torres Strait Islander males without such strategies. Future research should focus on evaluating the implementation of men specific utilization strategies. It is through evidence-based research that subsequent policies and programs can be made and implemented to improve Indigenous men's health.